Late Precambrian ignimbrites on the Avalon Peninsula, Newfoundland - Papezik, V. S. (Canadian Journal of Earth Sciences, 1969)
The predominantly volcanic Harbour Main Group of Late Precambrian age, forming a broad northerly trending belt in the central part of the Avalon Peninsula of Newfoundland, includes some well-developed ignimbrites. The ignimbrite sequence, best exposed in the western part of the volcanic belt, consists of ash-flow tuffs intercalated with tuff–breccias of various origins and minor volcanigenic sediments. Some of the ignimbrite sheets are densely welded, with distinct eutaxitic structures. Although the original glass is recrystallized, shard outlines are perfectly preserved and fragments of obsidian and perlite can be recognized; albite crystals are abundant, and quartz, augite, and biotite are present locally. The ignimbrites have been folded, faulted, and are now almost vertical. In composition, they range from rhyolites to dacites and are distinctly sodic.It is suggested that the ignimbrites may be derived from the gas-charged upper part of a granitic magma intruded into a pre-existing part of the Harbour Main volcanic pile; the lower, gas-poor part of the magma may have formed the present discordant "Holyrood batholith" of the Avalon Peninsula.